2019
DOI: 10.1073/pnas.1910827116
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for transcription activation by Crl through tethering of σ S and RNA polymerase

Abstract: In bacteria, a primary σ-factor associates with the core RNA polymerase (RNAP) to control most transcription initiation, while alternative σ-factors are used to coordinate expression of additional regulons in response to environmental conditions. Many alternative σ-factors are negatively regulated by anti–σ-factors. In Escherichia coli, Salmonella enterica, and many other γ-proteobacteria, the transcription factor Crl positively regulates the alternative σS-regulon by promoting the association of σS with RNAP … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…We point out that Cartagena and coworkers recently also reported a cryo-EM structure of a transcription activation complex comprising the E. coli RNAP core enzyme, Salmonella enterica serovar Typhimurium Crl and σ S (Cartagena et al, 2019). Our structure of E. coli Crl–TAC agrees well with this chimeric complex structure, and both structures show that Crl engages σ S -RNAP through a large interface with σ S 2 and a small interface with the RNAP core enzyme.…”
Section: Discussionmentioning
confidence: 80%
“…We point out that Cartagena and coworkers recently also reported a cryo-EM structure of a transcription activation complex comprising the E. coli RNAP core enzyme, Salmonella enterica serovar Typhimurium Crl and σ S (Cartagena et al, 2019). Our structure of E. coli Crl–TAC agrees well with this chimeric complex structure, and both structures show that Crl engages σ S -RNAP through a large interface with σ S 2 and a small interface with the RNAP core enzyme.…”
Section: Discussionmentioning
confidence: 80%
“…coli STIC crystals grow to full size in about 1 week and remain enzymatically active while present in the crystallization drops ( Liu et al., 2016 ). Crystallized STICs ( Figure 1 A) demonstrate essentially the same architecture as the STIC in solution ( Figure 1 B) ( Cartagena et al., 2019 ), but lack the contacts between the σ 4 domain and the promoter −35 element due to crystal packing. Compared with the STIC in solution, crystallized STICs show slightly tighter clamping by the pincers and a more localized trigger loop (TL) insertion domain.…”
Section: Resultsmentioning
confidence: 95%
“…Crl binds to stationary phase σ S and activates σ S -RNAP-mediated transcription, independently of the promoter sequence (Pratt and Silhavy, 1998;Bougdour et al, 2004). Although Crl does not bind to σ 70 because of the steric clash with σ 70 -NCR (Cartagena et al, 2019) it can activate σ 70 -dependent transcription (Gaal et al, 2006). As observed for RbpA, Crl facilitates transcription initiation by stabilizing the σ S -RNAP holoenzyme and stimulating RPo formation (Banta et al, 2013;Xu et al, 2019).…”
Section: Crlmentioning
confidence: 95%
“…As observed for RbpA, Crl facilitates transcription initiation by stabilizing the σ S -RNAP holoenzyme and stimulating RPo formation (Banta et al, 2013;Xu et al, 2019). Two high resolution cryo-EM-based structures of Crl-σ S -RNAP RPo have been recently described (Cartagena et al, 2019;Xu et al, 2019). Cartagena et al, suggested that Crl stabilizes σ S -RNAP by tethering σ S directly to RNAP though contacts with the β -clamp-toe domain (β -CT, residues 144-179).…”
Section: Crlmentioning
confidence: 97%
See 1 more Smart Citation